Além de um resíduo agroindustrial: valorizando a casca da castanha de caju por meio de estratégias de economia circular para produção de bioenergia, bioquímicos e painéis de partículas - Paiva, Evanice Medeiros de (2024)
This study was motivated by the large annual amount of cashew nutshells produced globally, which has raised environmental concerns about their proper disposal. Two technological routes have been proposed for the valorization of this lignocellulosic residue. The first one consisted of using physical-chemical characterization techniques, multicomponent kinetic analysis, thermodynamic study, and volatile product analysis to evaluate the potential of raw (RCNS) and pressed (PCNS) cashew nutshells in pyrolysis reactions. For this purpose, a thermogravimetric analyzer and an analytical pyrolyzer coupled with gas chromatography-mass spectrometry (Py-GC/MS) were used to perform the pyrolysis reactions. The pyrolysis behavior of RCNS and PCNS was accurately modeled using the Asym2sig deconvolution function, which identified five and four parallel devolatilization events, respectively. The average activation energies for the pyrolysis of RCNS and PCNS fell within the ranges of 63.8−249.3 and 91.1−167.4 kJ mol−1, respectively, as determined by four isoconversional methods (Friedman, Flynn–Wall–Ozawa, Kissinger–Akahira–Sunose, and Starink). Pre-exponential factors ranging from 4.2×108 to 6.9×1016 min−1 and from 4.8×108 to 3.2×1011 min−1 were estimated from the kinetic compensation effect for the pyrolysis of RCNS and PCNS, respectively. The method of master plots revealed that the most probable reaction models involved in the pyrolysis of RCNS and PCNS belong to the nucleation growth and nth-order reaction mechanisms. Analysis of the volatile products revealed that aliphatic hydrocarbons were the dominant components for condensable volatile products at 650 °C, while reaction temperatures of 450 and 550 °C favored the production of oxygenated compounds. The thermodynamic study confirmed the technical feasibility of converting both cashew nutshell residues into bioenergy and renewable chemicals due to the low energy barrier to overcome. The second technological route involved the production of sustainable particleboards using PCNS and eco-friendly phenolic resin obtained from the reaction of cashew nutshell liquid (CNSL) with formaldehyde at mass ratios of CNSL to formaldehyde of 1:0.25, 1:0.5, and 1:0.75 under acidic conditions and at 105 °C. The resin was characterized using techniques such as Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), High-Performance Liquid Chromatography (HPLC), and Nuclear Magnetic Resonance (NMR). The particleboards were subjected to tensile and flexural tests, and water absorption tests. Formaldehyde emission and biodegradability content of the particleboards were also evaluated. Among the tested conditions, the use of adhesive with CNSL/formaldehyde ratios of 1:0.25 and 1:0.50 resulted in E1 grade particleboards (with less than 8 mg/100 g of dry panel) in terms of formaldehyde emissions and significant improvements in mechanical properties. The biodegradability of PB25, PB50, and PB75 panels was 30%, 21%, and 20%, respectively, in 30 days. These results demonstrate the potential of cashew nutshell biomass and eco-friendly resin as adhesives in the particleboard industry. Both proposed technological routes show promise in valorizing cashew nutshell residues in the production of bioenergy, bio-based chemicals, and sustainable medium-density fiberboards. Furthermore, this study is aligned with the Sustainable Development Goals (SDGs) and can serve as a foundation for future large-scale implementation. This has the potential to generate jobs and promote a circular economy in the nut processing industry.